Feasibility study of using perfusion index to predict the timing of laryngeal mask insertion: an observational study - Weiwei Cai; Yuting Song; Fei Sun; Huiying Shao; Huanhuan Ni (BMC Anesthesiology)
Abstract Background Currently, no objective indicators are available to predict the optimal timing for laryngeal mask insertion. Anesthesia depth monitoring devices such as the Bispectral Index (BIS) are not widely applicable for day-surgery patients due to their high cost. Previous literature has reported a correlation between the perfusion index (PI) and the anesthesia depth. Thus, the aim of this study is to verify whether the PI can serve as an indicator for predicting the timing of laryngeal mask insertion. Methods This trial was conducted at a specialized pediatric hospital, with a final enrollment of 164 pediatric patients. After the children entered the room, baseline vital signs and PI1 were recorded. Three minutes after routine anesthesia induction, PI2 was recorded, and then a laryngeal mask was inserted. Then children were divided into the body movement group and the non-body movement group. The diagnostic efficacy of PI and the PI ratio for predicting the timing of laryngeal mask insertion were calculated using ROC curves. Results The area under the ROC curve (AUC) for using PI to predict the timing of laryngeal mask insertion was 0.641 (95% confidence interval, 0.542–0.740), P = 0.009, and the cutoff value was 4.37. When PI > 4.37 was used to predict the timing of laryngeal mask insertion, the sensitivity was 53.2%, and the specificity was 73.7%. The AUC for using the PI ratio to predict the timing of laryngeal mask insertion was 0.751 (95% confidence interval, 0.657–0.844), P < 0.001, and the cutoff value was 2.955. When the PI ratio > 2.955 was used to predict the timing of laryngeal mask insertion, the sensitivity was 85.7%, and the specificity was 63.2%. Conclusion The PI ratio is more suitable than PI alone for predicting the timing of laryngeal mask insertion. When PI increases to three times the baseline PI after induction, laryngeal mask insertion can be considered. Clinical trial registration : This trial was registered at the Chinese Clinical Trial Registry ( https://www.chictr.org.cn . Registration number ChiCTR2400083111, Weiwei Cai, 16 April 2024.)